Pengaruh Lama dan Suhu Aktivasi Terhadap Kualitas dan Struktur Kimia Arang Aktif Bagasse Effect of Time and Temperature Activation on Quality and Chemical Structure of Bagasse Activated Charcoal - Wawan Sujarwo (Jurnal Ilmu dan Teknologi Kayu Tropis, 2009)
The aim of this research was to determine the effect of time and temperature activation on the quality and chemical structure of bagasse activated charcoal. The study was designed in a completely random design with 3 x 3 factorial, each treatment was 5 times repeated. Bagasse was carbonized in an electrical retort at 400oC for 3.5 hours, then activated at 800oC, 900oC and 1000oC for 30, 60 and 90 minutes at each temperature. The quality of bagasse activated charcoal showed that the yield was 72.57 ~ 91.78%, 5.90 ~ 9.58% moisture content, 39.70 ~ 52.70% volatile matter, 18.40 ~ 25.30% ash content, 26.30 ~ 36.70% fixed carbon, 8.44 ~ 13.40% benzena adsorption, 1036.18 ~ 1474.33 (mg/g) iodium adsorption, 121.91 ~ 124.80 (mg/g) methylene blue adsorption. The surface area of bagasse activated charcoal was 250.45 m2/g. The FTIR analysis indicated that surface of bagasse activated charcoal contained bonding of C-X, S═O, C-N, N-H and C═C. The SEM analysis showed that there were wide pore diameter and plenty of pores. The application of bagasse activated charcoal at two villages reduced the colour, turbidity and iron contents until 65%, 30% manganese contents while hardness of water and pH did not change